2020
DOI: 10.2174/1567202617666200517105727
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphenolic Complex Attenuates Inflammatory Response and Blood- Brain Barrier Disruption

Abstract: Background: Cerebral ischemia causes strong inflammatory response. Neumentix is a dietary supplement containing 14.9% rosmarinic acid and 29.9% total phenolic content, which was proved to be beneficial against inflammatory response. Therefore, we investigated Neumentix’s effect on anti-inflammatory and blood brain barrier (BBB) disruption in transient middle cerebral artery occlusion (tMCAO) model mice. Methods: After the pretreatment of vehicle or Neumentix 134 mg/kg/d, intraperitoneal injection (i.p.) (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Multiple preclinical studies with SPE have demonstrated that SPE can reduce markers of oxidative stress and inflammation and promote neuroprotection in neural tissue. 18 – 20 Furthermore, SPE has been shown to modulate brain neurotransmitters in the mouse and promote neurogenesis in rat hippocampal neurons. 21 , 22 Clinical research has additionally shown that the extract is well tolerated and supports cognitive function improvements in both healthy young and older people.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple preclinical studies with SPE have demonstrated that SPE can reduce markers of oxidative stress and inflammation and promote neuroprotection in neural tissue. 18 – 20 Furthermore, SPE has been shown to modulate brain neurotransmitters in the mouse and promote neurogenesis in rat hippocampal neurons. 21 , 22 Clinical research has additionally shown that the extract is well tolerated and supports cognitive function improvements in both healthy young and older people.…”
Section: Introductionmentioning
confidence: 99%
“…Green tea polyphenols are able to reduce ischemia-elevated BBB permeability, as shown by Zhang and others in the rat occlusion model of cerebral ischemia [39]. Recent studies with commercially available extracts of plant-derived polyphenols, including Neumentix ® , confirmed their beneficial action on BBB integrity and ability to reduce the inflammatory response in mouse brain tissue after middle artery occlusion [40]. Polyphenolinduced sealing of the BBB during ischemia can mitigate the development of brain inflammation.…”
Section: Direct and Indirect Action Of Plant Polyphenolsmentioning
confidence: 85%
“…A plant polyphenol-rich diet not only mitigates the decline of cognitive functions during aging, but also these compounds are also considered helpful in the prevention and treatment of neuroinflammatory and neurodegenerative disorders. Numerous dietary polyphenols exhibit anti-inflammatory and antioxidant activity, which makes them potentially active in mitigating AD development [40,[46][47][48][49][50][51]. However, the results of AD-related experiments are not clear.…”
Section: The Impact Of Plant-derived Polyphenols On the Brain And Cog...mentioning
confidence: 99%
“…Neumentix [a spearmint-like extract, proprietary spearmint extract (PSE)] is a dietary supplement containing abundant rosmarinic acid and polyphenols (15). Some reports indicate that PSE has beneficial effects on learning and memory (16), anti-oxidative effects (17), antiinflammatory effects and attention enhancement (18).…”
Section: Introductionmentioning
confidence: 99%